2014
DOI: 10.1149/2.0181407jss
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polishing Parameters on Chemical Mechanical Planarization of C-Plane (0001) Gallium Nitride Surface Using SiO2and Al2O3Abrasives

Abstract: In this study, Chemical Mechanical Planarization (CMP) of (0001) GaN surface, using two different slurries containing colloidal silica and alumina as abrasive nanoparticles, has been reported. Effect of processing parameters, such as concentration of the oxidizer, downward pressure, head rpm, base rpm, pH of the slurries, and type and concentration of abrasive particles, on the material removal rate (MRR) and surface quality (roughness) have been studied in details. The maximum MRR has been found to be ∼39 nm/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 26 publications
5
63
0
Order By: Relevance
“…Fewer pits observed probably originate from the threading dislocation created during GaN growth and open up or became visible during CMP. The opening up of the dislocations due to the chemical etching effect during CMP is well known as observed in other investigations [28,44,45]. Regarding occasional scratches found after CMP using optimum condition, it is owing to mechanical abrasion by relatively harder Al 2 O 3 particles.…”
Section: Resultssupporting
confidence: 51%
See 2 more Smart Citations
“…Fewer pits observed probably originate from the threading dislocation created during GaN growth and open up or became visible during CMP. The opening up of the dislocations due to the chemical etching effect during CMP is well known as observed in other investigations [28,44,45]. Regarding occasional scratches found after CMP using optimum condition, it is owing to mechanical abrasion by relatively harder Al 2 O 3 particles.…”
Section: Resultssupporting
confidence: 51%
“…The CMP process parameters (for KMnO 4 /Al 2 O 3 based slurry) suggested by Taguchi-based grey relational analysis provides a relatively superior combination of MRR and RMS. Past works [21,23,26,28,46] based on traditional experimental techniques-varying one parameter at a time while keeping other parameters constanthave shown that a KMnO 4 /SiO 2 based slurry provides MRR b~40 nm/ h and RMS~b~10 nm. Though the MRR for c-plane GaN for the KMnO 4 /SiO 2 based slurry is significantly lower than that for KMnO 4 / Al 2 O 3 based slurry (from Taguchi-based grey relational analysis), the RMS for KMnO 4 /SiO 2 or H 2 O 2 /SiO 2 based slurry is significantly superior.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Highly surface active cationic and/or anionic surfactants are adsorbed on the particle surfaces, which shield the surface charges of the particles due to high ionic strength. In our previous work, and from the literature, KMnO 4 has been proven a good oxidizer for CMP of polar and non-polar GaN surfaces [20,21]. The function of KMnO 4 in GaN CMP is to participate and promote the chemical reaction between the slurry and GaN surface thereby forming a relatively soft oxide (may be Ga 2 O 3 ) layer on the surface, which subsequently is removed by the dissolution and/or mechanical abrasion of polishing.…”
Section: Effect Of Surfactant On Materials Removal Rate (Mrr)mentioning
confidence: 97%
“…Khushnuma et al reported maximum MRR of ∼85 nm/hr on polar GaN wafer for slurry containing 3.75 wt% Al 2 O 3 and 0.3 M oxidizer concentration but no surfactant or electrolyte in the slurry. Material removal rates of 1.14 m/hr and 1.85 m/hr for non-polar (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and semi-polar (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) GaN surfaces, respectively, have been achieved using an abrasive free chemical mechanical planarization [20,21]. Studies of surfactant adsorption have typically focused on conditions where there is clear electrostatic driving force for adsorption; i.e., where surfactants have opposite charge to those of metal oxide surfaces [22].…”
Section: Introductionmentioning
confidence: 99%